Is The Indonesian Market React to The Sukuk Issuance Announcement? - Muhammad Qomaruddin Ridwan; Zuni Barokah (Universitas Muhammadiyah Surakarta, 2022)
This study examines market reaction following the announcement of Sukuk issuance by listed companies in the Indonesia Stock Exchange between 2013 and 2017. There were twenty-three Sukuk publishing announcements during this period. Our findings indicate that there are two events that have abnormal returns on the day around the announcement of Sukuk issuance, but overall there are no abnormal returns. There was no change in trading volume on the days before and after the announcement of the Sukuk issuance both as a whole event and each event. Lastly, we can not find any significant association between the type of Sukuk (i.e., ijarah) and the cumulative abnormal returns. This study examines market reaction following the announcement of sukuk issuance by listed companies in the Indonesia Stock Exchange between 2013 and 2017. T here were twenty-three sukuk publishing announcements during this period. Our findings indicate that there are two events that have abnormal returns on the day around the announcement of sukuk issuance, but overall there are no abnormal returns. There was no change in trading volume on the days before and after the announcement of the sukuk issuance both as a whole event and each event. Lastly, we can not find any significant association between the type of sukuk (i.e., ijarah) and the cumulative abnormal returns.